Phytotoxicity of cadmium on the germination and initial growth of Ecuadorian maize varieties (Bioagro, 2021)
Cadmium (Cd) is a pollutant that inhibits seed germination and decreases crop productivity. In Ecuador, contamination by this metal has been demonstrated in some agricultural soils. The objective of this research was to measure the effects of Cd on the germination and growth of the maize varieties INIAP-101, INIAP-122, INIAP-151, INIAP H-551, INIAP H-553, INIAP-180, and a native variety to the Manabí province in Ecuador (Autóctona). Seeds of the varieties were exposed to 0, 0.25, 0.5, 1, 2, 4, and 8 mg∙L-1 CdNO3 for 8 days and it was determined the germination start day and percentage, and length of radicle and hypocotyl. The effect of Cd was evaluated by calculating the tolerance and phytotoxicity indices. The germination percentage decreased by 37.5 in INIAP H-551, and only slightly in the Autónoma, at level of 1 mg∙L-1; the other varieties were not affected. According to the tolerance index, the most tolerant variety to Cd was the Autónoma, and the least tolerant were INIAP-101 and INIAP-122. The integral phytotoxicity index showed the toxicity of Cd in the following order: INIAP-101, INIAP H-551, INIAP-122, INIAP H-553, INIAP -180, INIAP-151, and the least affected was the Autónoma. Farmers are advised to analyze the cadmium concentration in the soil before cultivation and, depending on the degree of contamination, avoid growing the less tolerant varieties.
Keywords: Heavy metals; tolerance; Zea mays